Water trajectories through non-networked infrastructure: insights from peri-urban Dar es Salaam, Cochabamba and Kolkata. Issue 1 (2nd January 2017) - Allen, Adriana; Hofmann, Pascale; Mukherjee, Jenia; Walnycki, Anna
Abstract : For many urbanites, infrastructural uncertainty refers to 'predictable shocks' rather than constituting a quotidian experience. By contrast, for the peri-urban poor, the sources of uncertainty underpinning water and sanitation services are endless: uncertainty about cost, about being evicted and indeed about ever becoming connected to networked systems. Drawing on a number of case studies, we argue that across the urban global south, the future is not one of networked systems but rather one of 'infrastructural archipelagos' that need to be thoroughly understood in order to bridge the growing gap between everyday and large infrastructural planning practices.